The riverfront redevelopment framework based on the riverfront ecological characteristics for Sungai Langat, Selangor - Nabilah binti Redzuan (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Channelization of river and landscape beautification occurred along the riverbank are parts of the development that occurred in the urban cities around the world, including urban cities in Malaysia. Many redevelopments done were a solution to prevent natural catastrophe such as flood from worsening and cater people's needs without considering the nature of river. However, the redevelopments were still not enough to bring back the natural condition of the river. Hence, realizing the adverse effects towards the riverfront, many developed countries have started to redevelop the riverfront ecologically in order to ensure the developed riverfront in urban areas can be closely restored to its natural condition. However, the incorporation of principles of ecological riverfront design in redevelopment of riverfront is still minimally addressed especially in Malaysia. Hence, this research aimed to develop a riverfront redevelopment framework based on the riverfront ecological characteristics, with a case study of Sungai Langat, Selangor. There are three (3) main research objectives that need to be achieved, which are (i) to identify the principles of the ecological riverfront design that is suitable for the urban ecosystem in Sungai Langat, Selangor, (ii) to examine the current characteristics of the riverfront development in the urban ecosystem of Sungai Langat, Selangor; and (iii) to generate the framework that complements the redevelopment of riverfront in the urban ecosystem based on the riverfront ecological characteristics for Sungai Langat, Selangor. Qualitative method using case study as part of qualitative research was employed. All data were collected through secondary data such as books, journals and reports; and primary data collected through content analysis and structured interviews conducted among the selected experts. Content analysis was also used to analyse the data, which led in identifying the principles of the ecological riverfront design that is suitable for the urban ecosystem in Sungai Langat, Selangor, and examining the characteristics of riverfront development in the urban ecosystem of Sungai Langat, Selangor. The findings indicated that the principles of ecological riverfront design were classified into four stages of principles, which are the general, planning, design and implementation. Not all principles of ecological riverfront design developed by other developed countries were suitable to be applied in a Malaysia context. The current characteristics of riverfront development played an important role in guiding the experts on suggesting the suitable principles in Sungai Langat, Selangor. According to the experts, there were three general principles, seven planning principles, eight design principles and four implementation principles identified suitable for Sungai Langat, Selangor. Thus, the riverfront redevelopment framework could be developed based on the riverfront ecological characteristics in Sungai Langat, Selangor according to the experts' opinions, as their expertise is important in developing the framework. In summary, the methodology of developing the framework could become a reference for architects, planners, engineers and other related professional bodies to reconsider the ecological aspect of riverfront while planning and creating the urban spaces along the riverbank, hence, promoting ecological redevelopment of riverfront in the urban cities.